A Decision Tree Based Methodology for Evaluating Creativity in Engineering Design - Kershaw, Trina C.; Bhowmick, Sankha; Seepersad, Carolyn Conner; Hölttä-Otto, Katja (Frontiers in Psychology, 2019)
Multiple metrics have been proposed to measure the creativity of products, yet there is still a need for effective, reliable methods to assess the originality of new product designs. In the present article we introduce a method to assess the originality of concepts that are produced during idea generation activities within engineering design. This originality scoring method uses a decision tree that is centered around distinguishing design innovations at the system level. We describe the history and the development of our originality scoring method, and provide evidence of its reliability and validity. A full protocol is provided, including training procedures for coders and multiple examples of coded concepts that received different originality scores. We summarize data from over 500 concepts for garbage collection systems that were scored by Kershaw et al. (2015). We then show how the originality scoring method can be applied to a different design problem. Our originality scoring method, the Decision Tree for Originality Assessment in Design (DTOAD), has been a useful tool to identify differences in originality between various cohorts of Mechanical Engineering students. The DTOAD reveals cross-sectional differences in creativity between beginning and advanced students, and shows longitudinal growth in creativity from the beginning to the end of the undergraduate career, thus showing how creativity can be influenced by the curriculum. The DTOAD can be applied to concepts produced using different ideation procedures, including concepts produced both with and without a baseline example product, and concepts produced when individuals are primed to think of different users for their designs. Finally, we show how our the DTOAD compares to other measurements of creativity, such as novelty, fixation, and remoteness of association.